THE RELATIONSHIP BETWEEN PHYSICAL EXERCISE AND MENTAL HEALTH IN STUDENTS (CIPEEX, 2022)
INTRODUCTION: MENTAL HEALTH REFERS TO A WELLBEING IN WHICH THE INDIVIDUAL DEVELOPS PERSONAL SKILLS, CAN COPE WITH THE STRESSES OF LIFE, WORKS PRODUCTIVELY AND IS ABLE TO CONTRIBUTE TO THE COMMUNITY, AND PHYSICAL EXERCISE IS A POSSIBLE ALLY TO MAINTAIN THIS STATE OF WELLBEING. OBJECTIVE: MINI INTEGRATIVE REVIEW THAT AIMED TO VERIFY THE EXISTENCE OF A RELATIONSHIP BETWEEN THE PRACTICE OF PHYSICAL EXERCISES AND THE MAINTENANCE OF MENTAL HEALTH IN STUDENTS. METHODS: FIVE ARTICLES FROM THE SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND GOOGLE ACADEMIC DATABASES WERE USED, FOUND THROUGH THE DESCRIPTORS "MENTAL HEALTH", "PHYSICAL EXERCISE" AND "STUDENTS". RESULTS: IT WAS VERIFIED, THROUGH THE FIVE ARTICLES, THAT PHYSICAL EXERCISE IS REALLY ESSENTIAL TO MAINTAIN MENTAL HEALTH AND AVOID THE ONSET OF MENTAL ILLNESS AND OTHER PSYCHOLOGICAL PATHOLOGIES IN COLLEGE STUDENTS. THUS, IT WAS OBSERVED THAT SEVERAL MODALITIES OF PHYSICAL EXERCISE REDUCE STRESS, RELIEVE DAILY PRESSURE, IMPROVE SLEEP, MEMORY SKILLS, THINKING AND PERCEPTION, AND IMPROVE THE PHYSICAL FUNCTION OF THESE YOUNG PEOPLE. SO, IT WAS POSSIBLE TO VERIFY THAT ALL AUTHORS EVIDENCED THAT THERE IS A RELATIONSHIP BETWEEN THE PRACTICE OF PHYSICAL EXERCISES AND THE MAINTENANCE OF MENTAL HEALTH IN STUDENTS. CONCLUSION: IT IS CONCLUDED THAT THE PRACTICE OF THESE EXERCISES SHOULD BE CONSIDERED, SINCE THERE ARE SIGNIFICANT RESULTS IN THE PERFORMANCE AND MENTAL HEALTH OF COLLEGE STUDENTS; HOWEVER, THE USE OF MEDICATION, IF NECESSARY, SHOULD NOT BE RULED OUT IN ORDER TO ENHANCE THESE RESULTS.
Keywords: mental health; physical exercise; students